Analyzing the Gap between Conventional and TPACK-Based Assessment in Islamic Religious Education - Nur Azizatul Haqiah; Abdul Munip (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the gap between the objectives of Islamic Religious Education (PAI) and assessment practices in schools, as well as to examine teacher-related factors from the perspective of Technological Pedagogical Content Knowledge (TPACK) and propose potential solutions. This research employs a qualitative approach using a library research method. Data were collected from relevant academic sources, including journal articles and scholarly books published between 2021 and 2026. The data were analyzed using a Systematic Literature Review (SLR) combined with content analysis. The findings reveal a significant gap between the holistic objectives of PAI and assessment practices that predominantly focus on cognitive aspects. This gap is influenced by teachers’ limited ability to integrate technological, pedagogical, and content knowledge within the TPACK framework. As a result, assessment practices remain less authentic and fail to comprehensively measure students’ affective and psychomotor competencies. The study highlights that strengthening teachers’ TPACK competence is essential to developing more authentic, contextual, and technology-based assessments. This research contributes conceptually to the development of TPACK-based assessment in Islamic education and provides insights for improving the quality of educational evaluation in the digital era. Keywords: Islamic Religious Education Assessment; Assessment Gap; TPACK; Teacher Competence; Technology-Based Learning